Drobni przedsiębiorcy w wojewodztwie lubuskim = Small business people in the Lubuskie region - Gandecka, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article shows specific factors of the Lubuskie province as a region of economic initiatives in the period of political system transformation. The research was carried out in 2005. People under 35 years of age representing small business were researched. The studies made it possible to analyse the reasons for and circumstances of setting up an independent business and find opinions about Lubuskie as an area of starting and running an independent enterprise.
Keywords: województwo lubuskie; small business; przedsiębiorczość; małe przedsiębiorstwo; badania